THE RESEARCH OF ASSOCIATIONS IN LINGUISTICS - I. M. Akhmad (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2015)
The paper deals with the characteristics of the associative-semantic relationships lexemes. Traditionally, the study of lexical system is carried out by examining the lexico-semantic paradigms, most of which are formed on the basis of integral-differential constraints lexemes. Furthermore, these lexical categories are related to the situation themed items. Different nature organizations have union-associated words. Their comparison with conventional paradigms is very difficult. However, studies have shown that the relationship between the associated words can also have a semantic basis. The study of semantically close and associated words is an actual objective of linguistics at the moment. Scientists reveal the principles of classification-associated units of language, their typology, semantic relationships between associations and associates. As a result of these studies, together with the generally recognized rules and definitions, there is a new type of lexical paradigm which is introduced by associative-semantic group, whose members are parts of the associative field and thus contain the same semantic structure of semes. Semantic approach to the study of associated words is promising because it allows a researcher to expand understanding of the lexico-semantic paradigmatic, the principles of the systematization of vocabulary. In the future, there are prospective of studying associative-semantic links between members of different thematic, lexico-semantic groups of words of different parts of speech.